Unraveling the environmental and genetic interactions in atherosclerosis: Central role of the gut microbiota. Issue 2 (August 2015) - Org, Elin; Mehrabian, Margarete; Lusis, Aldons J.
Abstract: Recent studies have convincingly linked gut microbiota to traits relevant to atherosclerosis, such as insulin resistance, dyslipidemia and inflammation, and have revealed novel disease pathways involving microbe-derived metabolites. These results have important implications for understanding how environmental and genetic factors act together to influence cardiovascular disease (CVD) risk. Thus, dietary constituents are not only absorbed and metabolized by the host but they also perturb the gut microbiota, which in turn influence host metabolism and inflammation. It also appears that host genetics helps to shape the gut microbiota community. Here, we discuss challenges in understanding these interactions and the role they play in CVD. Highlights: Gut microbiota influence lipid metabolism, insulin resistance, and systemic inflammation. Gut microbiota modulate the effects of dietary and, most likely genetic factors on atherosclerosis. Systems genetics approaches should be useful in dissecting the complexities of host–microbiota interactions.